2003
DOI: 10.1038/nature01596
|View full text |Cite
|
Sign up to set email alerts
|

DNA triplet repeats mediate heterochromatin-protein-1-sensitive variegated gene silencing

Abstract: Gene repression is crucial to the maintenance of differentiated cell types in multicellular organisms, whereas aberrant silencing can lead to disease. The organization of DNA into chromatin and heterochromatin is implicated in gene silencing. In chromatin, DNA wraps around histones, creating nucleosomes. Further condensation of chromatin, associated with large blocks of repetitive DNA sequences, is known as heterochromatin. Position effect variegation (PEV) occurs when a gene is located abnormally close to het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
239
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(252 citation statements)
references
References 30 publications
11
239
1
1
Order By: Relevance
“…First, tsDNA formation has been observed to correlate well with the transcription repression of frataxin and the pathogenesis (24). Our finding offers an explanation that this gene-silencing structure leading to Friedreich's ataxia, the most common inherited ataxia, can in fact be aggregated DNA triplexes effecting heterochromatin-like inhibition (38). Second, DNA triplex motifs occur frequently in eukaryotic genomes (up to 1%) (24,39).…”
Section: Discussionmentioning
confidence: 80%
“…First, tsDNA formation has been observed to correlate well with the transcription repression of frataxin and the pathogenesis (24). Our finding offers an explanation that this gene-silencing structure leading to Friedreich's ataxia, the most common inherited ataxia, can in fact be aggregated DNA triplexes effecting heterochromatin-like inhibition (38). Second, DNA triplex motifs occur frequently in eukaryotic genomes (up to 1%) (24,39).…”
Section: Discussionmentioning
confidence: 80%
“…One reason why long repeats might be selected against near housekeeping genes is that an abundance of these repeats might reduce gene expression via heterochromatin spread. Long transposons (Lyon, 1998;Marahrens, 1999;Bailey et al, 2000;Allen et al, 2003;Lippman et al, 2004;Sun et al, 2004) and long tracts of tandem repeats (Pieretti et al, 1991;Hansen et al, 1997;Saveliev et al, 2003) have been implicated in gene silencing via the spread of heterochromatin. Another reason why LINE-1 and other long transposons might be scarce around housekeeping genes is that the euchromatin could spread into the transposons and activate their internal promoters (Swergold, 1990;Minakami et al, 1992;Leib-Mösch and Seifarth, 1995;Speek, 2001;Athanikar et al, 2004).…”
Section: Long Repeats May Be Disadvantageous To Nearby Housekeeping Gmentioning
confidence: 99%
“…Whereas an involvement of mutp53 in the pathophysiology of neurodegenerative diseases seems to be rather unlikely, a more intriguing possibility is that the binding of (CTG CAG) tracts by mutp53 proteins could be relevant for establishing specific patterns of chromatin structure in cancer cells. In light of the propensity of (CTG CAG) tracts to function as nucleosome positioning elements (Wang and Griffith, 1995), and to stimulate the formation of heterochromatin throughout the genome irrespective of chromosomal location (Saveliev et al, 2003), it is tempting to hypothesize that wtp53 or mutp53 by associating with (CTG CAG) tracts may contribute to the establishment (or maintenance) of a repressive state of the chromatin. Interestingly, heterochromatin protein 1, involved in the propagation of a heterochromatic structure (Lachner et al, 2001) including those formed by (CTG CAG) tracts (Saveliev et al, 2003), was recently found to mediate the developmental mutp53 actions on DNA E Kim and W Deppert repression of the alpha-fetoprotein gene by wtp53 (Nguyen et al, 2005).…”
Section: Direct Binding Of Mutp53 To Dnamentioning
confidence: 99%
“…In light of the propensity of (CTG CAG) tracts to function as nucleosome positioning elements (Wang and Griffith, 1995), and to stimulate the formation of heterochromatin throughout the genome irrespective of chromosomal location (Saveliev et al, 2003), it is tempting to hypothesize that wtp53 or mutp53 by associating with (CTG CAG) tracts may contribute to the establishment (or maintenance) of a repressive state of the chromatin. Interestingly, heterochromatin protein 1, involved in the propagation of a heterochromatic structure (Lachner et al, 2001) including those formed by (CTG CAG) tracts (Saveliev et al, 2003), was recently found to mediate the developmental mutp53 actions on DNA E Kim and W Deppert repression of the alpha-fetoprotein gene by wtp53 (Nguyen et al, 2005). Keeping in mind that the interactions of wtp53 and of mutp53 with DNA appear to intimately connect with chromatin modifying activities (discussed in the previous section), it would be interesting to examine whether the binding of wtp53 or mutp53 contributes to the regulation of chromatin structure via (CTG CAG) tracts and whether such binding may be relevant for regulation of gene expression.…”
Section: Direct Binding Of Mutp53 To Dnamentioning
confidence: 99%